The Ecology and Evolutionary Dynamics of Meiotic Drive. (April 2016) - Lindholm, Anna K.; Dyer, Kelly A.; Firman, Renée C.; Fishman, Lila; Forstmeier, Wolfgang; Holman, Luke; Johannesson, Hanna; Knief, Ulrich; Kokko, Hanna; Larracuente, Amanda M.; Manser, Andri; Montchamp-Moreau, Catherine; et al.
Abstract : Meiotic drivers are genetic variants that selfishly manipulate the production of gametes to increase their own rate of transmission, often to the detriment of the rest of the genome and the individual that carries them. This genomic conflict potentially occurs whenever a diploid organism produces a haploid stage, and can have profound evolutionary impacts on gametogenesis, fertility, individual behaviour, mating system, population survival, and reproductive isolation. Multiple research teams are developing artificial drive systems for pest control, utilising the transmission advantage of drive to alter or exterminate target species. Here, we review current knowledge of how natural drive systems function, how drivers spread through natural populations, and the factors that limit their invasion. Trends: Both naturally occurring and synthetic 'meiotic drivers' violate Mendel's law of equal segregation and can rapidly spread through populations even when they reduce the fitness of individuals carrying them. Synthetic drivers are being developed to spread desirable genes in natural populations of target species. How ecology influences the population dynamics of meiotic drivers is important for predicting the success of synthetic drive elements. An enduring puzzle concerns why some meiotic drivers persist at stable, intermediate frequencies rather than sweeping to fixation. Drivers can have a wide range of consequences from extinction to changes in mating system.